2013
DOI: 10.4236/ijg.2013.45080
|View full text |Cite
|
Sign up to set email alerts
|

Swelling Measurements of a Low Rank Coal in Supercritical CO<sub>2</sub>

Abstract: Coal swelling in the presence of water as well as CO 2 is a well-known phenomenon, and these may affect the permeability of coal. Quantifying swelling effects is becoming an important issue to verify the suitability of particular coal seams for CO 2 -enhanced coal bed methane recovery projects. In this report, coal swelling experiments using a visualization method in the CO 2 supercritical conditions were conducted on crushed coal samples. The measurement apparatus was designed specifically for the present swe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…The storage of CO 2 in deep unmineable coal seams is currently identified as a potential approach to the minimization of anthropogenic CO 2 in the atmosphere. Numerous research studies have therefore been commenced on this method, particularly related to the alteration of coal seam properties (hydro-mechanical properties) upon CO 2 injection. According to these studies, CO 2 has greater potential to be adsorbed into the coal mass compared to the existing CH 4 in the coal matrix, which confirms the greater storage potential for CO 2 in underground coal reservoirs…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The storage of CO 2 in deep unmineable coal seams is currently identified as a potential approach to the minimization of anthropogenic CO 2 in the atmosphere. Numerous research studies have therefore been commenced on this method, particularly related to the alteration of coal seam properties (hydro-mechanical properties) upon CO 2 injection. According to these studies, CO 2 has greater potential to be adsorbed into the coal mass compared to the existing CH 4 in the coal matrix, which confirms the greater storage potential for CO 2 in underground coal reservoirs…”
Section: Introductionmentioning
confidence: 99%
“…However, the studies carried out for low rank coal used only low injecting pressures and examined only gas and liquid states of CO 2 . Although Anggara et al conducted swelling experiments on crushed lignite from Indonesia for supercritical CO 2 (up to 10 MPa) using coal blocks of 30 × 10 × 10 mm 3 , they did not consider the effect of confining pressure on coal swelling. The incorporation of this confining pressure effect is important for the correct identification of the swelling effect in field stress environments.…”
Section: Introductionmentioning
confidence: 99%
“…There are some important phenomena associated with geological storage of CO 2 in coal seams. The great adsorption capacity of supercritical CO 2 can influence the surface areas and functional groups microscopically, ,, which induces great swelling macroscopically. Comparing several specific areas, Kutchko et al found there were no significant changes in these pore areas considering 5% offset, while changes in the micro- and mesopore scale was observed using CO 2 adsorption and nitrogen BET measurements . Day concluded that swelling was reversible after removing the gas …”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have been conducted to investigate the permeability and swelling induced by adsorption. Permeability of CO 2 in brown coal was studied by Ranathunga et al , CO 2 adsorption-induced swelling was investigated at different temperatures and pressures and microcleat closure was observed by Zhang et al Eventually, the permeability of coal decreases. In deep coal seams, CO 2 is in the supercritical state as shown in Figure , which facilitates the low volume of CO 2 occupation because of high density of supercritical CO 2 . , CO 2 is a nonpolar molecule, and it can act as a solvent . There are some changes with the injection of supercritical CO 2 in coal.…”
Section: Introductionmentioning
confidence: 99%